2020
DOI: 10.51724/ijpce.v12i1.86
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and Persistent Issues in the Delivery of Asynchronous Non-Traditional Undergraduate Physics Experiments

Abstract: Remote physics laboratory activities are common tools of use in physics in traditional, online, and distance education to enhance student learning. Although these offerings necessitated by technological advances, spur innovation and improvement in undergraduate physics education, their use as stand-alone substitutes for instructor-guided physical laboratory experiments remain the center of debate and research. This paper discusses the effectiveness of the current pedagogic issues in the delivery and learning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Even when HALK labs are used, the potential for limited hands-on interaction with experimental apparatus is real (Fox et al, 2020). Nevertheless, other researchers (Fox et al, 2020;Sauter et al, 2013;Sithole at al., 2020), argue that the key to a successful remote laboratory learning experience lies in the design of the lab activities. Automatically adapting the traditional laboratory exercises directly to the online environment poses challenges to both the students and the instructor.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Even when HALK labs are used, the potential for limited hands-on interaction with experimental apparatus is real (Fox et al, 2020). Nevertheless, other researchers (Fox et al, 2020;Sauter et al, 2013;Sithole at al., 2020), argue that the key to a successful remote laboratory learning experience lies in the design of the lab activities. Automatically adapting the traditional laboratory exercises directly to the online environment poses challenges to both the students and the instructor.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the design of remote labs should factor in the availability of tools needed and software limitations. In the case of OSCBS, the software update is a significant challenge for remote learning (Sithole et al, 2020). A further challenge to the use of OSCBS is that open-source lab software is subject to change over time, which may require periodic updating of experimental procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, Dark (2021) and Nogueira and Hernandes (2021) demonstrated that both virtual and physical distance physics laboratory experimentations can possibly be conducted by students at home. In fact, Sithole et al (2020) demonstrated that distance laboratories are not uncommon strategies to deliver physics instruction even before the COVID-19 pandemic. However, during the pandemic, the situation is worse due to lack of or slow communication between teachers and learners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, proponents of hands-on labs often value design skills and social interaction [4], while proponents of remote labs often value learning content and theory [7]. Other possible benefits of remote lab experiences include providing more flexibility [8] and increasing accessibility for students who are part-time, have disabilities, or have caring responsibilities [9].…”
Section: Introductionmentioning
confidence: 99%